2015
DOI: 10.15560/11.4.1706
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of marine larval trematodes (Digenea) in molluscs from Argentina, Southwestern Atlantic coast

Abstract: A checklist of cercariae parasitizing marine molluscs from Patagonian coast, Argentina, based on literature sources and new records here presented. In total, cercariae of 31 species of marine digeneans, including 11 new records here presented, are known to infect 20 species of molluscs (14 in nine gastropods species; 17 in 11 bivalve species). These records include two species of Aporocotylidae, four Bucephalidae, one Fellodistomidae, five Gymnophallidae, one Hemiuroidea, four Lepocreadiidae, two Microphallida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…To date, 23 species of cercariae belonging to this family have been described (Villot, 1875;Macfarlane, 1951;Ito & Shimura, 1980;Stunkard 1980a, b;Watson, 1984;Aguirre-Macedo & Kennedy, 1999;Hassanine, 2006;Averbuj & Cremonte, 2010 and references therein). Six of them were recorded in the Southern Hemisphere and three were recorded in the Argentinean Sea, including the cercariae here described (Martorelli, 1991;Averbuj & Cremonte, 2010;Bagnato et al, 2015). Lepocreadiidae gen. et sp.…”
Section: Journal Of Helminthologymentioning
confidence: 89%
See 3 more Smart Citations
“…To date, 23 species of cercariae belonging to this family have been described (Villot, 1875;Macfarlane, 1951;Ito & Shimura, 1980;Stunkard 1980a, b;Watson, 1984;Aguirre-Macedo & Kennedy, 1999;Hassanine, 2006;Averbuj & Cremonte, 2010 and references therein). Six of them were recorded in the Southern Hemisphere and three were recorded in the Argentinean Sea, including the cercariae here described (Martorelli, 1991;Averbuj & Cremonte, 2010;Bagnato et al, 2015). Lepocreadiidae gen. et sp.…”
Section: Journal Of Helminthologymentioning
confidence: 89%
“…The species described in this study were recorded previously by Bagnato et al (2015), summarizing a total of 12 digenean larval species found in Puerto Deseado. Of 11 digenean larvae that use snails as the first intermediate host, seven use shorebirds as the definitive host (two Microphallidae, one Notocotylidae, two Renicolidae, one Philophtalmidae and one Schistosomatidae) and the other four use fish (one Hemiuroidea, two Lepocreadiidae and one Zoogonidae) (Gibson et al, 2002;Jones et al, 2005;Bray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on parasites in coexisting bivalves are scarce and mostly consider metazoan parasites (Bagnato et al, 2015). The host range of a parasite may be due to phylogenetic, ecological, physiological and immunological factors (Detwiler and Janovy, 2008).…”
Section: Discussionmentioning
confidence: 99%